Physio-chemical and mineralogical characteristic of Rhu Tapai Soil Series - Suhaimin, Nur Suhada (2015)
Sandy beach ridges are dominated by soils having sand texture which are locally named BRIS (Beach Ridges Interspersed with Swales) soil. Coastal plains of Peninsular Malaysia had been inundated by seawater ,coastal zone had undergone progradation that led to formation of wide beach ridges plains along state of Peninsular Malaysia. More than 90% of the composition of BRIS soil is sand and the soil is considered practically worthless for agricultural purposes. The study area was conducted along the Kelantan-Terengganu Coastal Plains, Peninsular Malaysia. Rhu Tapai series is one of the BRIS soil series. The objectives of this study are to determine mineralogy in Rhu Tapai series and to study the physical and chemical properties of these series. This series located on second ridge occuring some distance away from the first ridge. Soil undergo process podzolisation that result formation of spodic horizon at depth 0-50 cm. For Rhu Tapai series that was Spodosols, soil pits were dug and samples were taken according to its genetic horizons. The analysis for physical properties, chemical properties and mineral identification were carried out. Methodology to determine mineral in soil will be by X-ray diffraction (XRD) that is the single most important method for identifying the variety of mineral species present in soils. Soil physical and chemical data obtained were subjected to analysis of variance (ANOVA), and the means were separated using Least Significant Different (LSD) test. The result showed low clay and silt content, high porosity, low water retention and lack of soil nutrients such as nitrogen and phosphorous are all the characteristic of the soil which limit the growth on crops. The mineralogy found were dominantly by quartz and presence of kaolinite, hematite, feldspar, gibbsite and goethite in small amounts in soil. Soil productivity of this soil can be improve by apply plant waste as mulching and removing the eluvial horizon in order to reach the organic rich spodic layer in order to soil susceptible for cropping.